Proportion and distribution of neurotransmitter-defined cell types in the ventral tegmental area and substantia nigra pars compacta - William S. Conrad; Lucie Oriol; Grace J. Kollman; Lauren Faget; Thomas S. Hnasko (Addiction Neuroscience, 2024)
Most studies on the ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) have focused on dopamine neurons and their role in processes such as motivation, learning, movement, and associated disorders such as addiction and Parkinson's disease. However there has been increasing attention on other VTA and SNc cell types that release GABA, glutamate, or a combination of neurotransmitters. Yet the relative distributions and proportions of neurotransmitter-defined cell types across VTA and SNc has remained unclear. Here, we used fluorescent in situ hybridization in male and female mice to label VTA and SNc neurons that expressed mRNA encoding the canonical vesicular transporters for dopamine, GABA, or glutamate: vesicular monoamine transporter (VMAT2), vesicular GABA transporter (VGAT), and vesicular glutamate transporter (VGLUT2). Within VTA, we found that no one type was particularly more abundant, instead we observed similar numbers of VMAT2+ (44 %), VGAT+ (37 %) and VGLUT2+ (41 %) neurons. In SNc we found that a slight majority of neurons expressed VMAT2 (54 %), fewer were VGAT+ (42 %), and VGLUT2+ neurons were least abundant (16 %). Moreover, 20 % of VTA neurons and 10 % of SNc neurons expressed more than one vesicular transporter, including 45 % of VGLUT2+ neurons. We also assessed within VTA and SNc subregions and found remarkable heterogeneity in cell-type composition. And by quantifying density across both anterior-posterior and medial-lateral axes we generated heatmaps to visualize the distribution of each cell type. Our data complement recent single-cell RNAseq studies and support a more diverse landscape of neurotransmitter-defined cell types in VTA and SNc than is typically appreciated.